An architectural approach towards a sustainable development - Parashar, Rinku (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Sustainable development is an organising principle for human life on a planet. It can actually be defined as a development that meets the needs of the present without compromising the ability of future generations to meet their own needs. The broader topic “Sustainability” is believed to be supported on three pillars, the environmental sustainability, economic sustainability and social sustainability. The burning issues which are being confronted today are, Global warming of atmosphere and green-house gases accumulation, Ozone layer thinning away with all negative impacts, which are the result of going against the ecological laws. In order to answer to all these boiling issues, major steps have to be taken at the root level itself. The first step needs to be the identification as to, what is environmentally desirable and what are the most feasible options for achieving them be it physical, economic, social and technological. Majorly the effort which has to be initiated with, is identification of processes, which deal with various activities for creation of the plans seeking to identify what is environmentally desirable. Wise use of activity and resources will have a positive effect on the environment. Without proactive environmental management, development is unlikely to be sustainable and people will be more vulnerable to disasters. Thus a sincere effort should be made to stretch what nature provides to the optimum and maintain that expansion indefinitely without environmental breakdown, in order to maximize human well-being, security and adaptability. Due to the rapid increase in construction activity many negative impacts are being observed. Buildings that are designed and used today contribute to serious environmental problems due to excessive consumption of energy and other natural resources. An integrated approach towards the building design should be adopted which will result in energy resource efficiency. Present Research paper will include the process, steps and techniques a designer in the present day should incorporate in his design, right from the site selection to the finishing stage so as to safeguard the future of human beings thus accomplish the goal of sustainability. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>